1995
DOI: 10.3109/00016349509021207
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of omphalocele associated with umbilical cord cyst

Abstract: The umbilical cord cysts most commonly associated with omphaloceles are pseudocysts and allantoic cysts. Among our three cases and the six other cases published in the literature, four out of these nine cases were trisomy 18. Prenatal diagnosis of omphaloceles or umbilical cord cysts by ultrasound warrants cytogenetic analysis and detailed sonogram to rule out the possible combination of both abnormalities and trisomy 18. If an omphalocele is associated with a large umbilical cord cyst and a normal karyotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…3 Coexistence of these cysts with omphalocele has been observed earlier in many instances. 3,7 In these patients, though these cysts were reported found to exist close to the omphalocele, but were never found inside the sac. Umbilical cord cysts are commonly seen in patients with trisomy 18, 13 or other aneuploidy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…3 Coexistence of these cysts with omphalocele has been observed earlier in many instances. 3,7 In these patients, though these cysts were reported found to exist close to the omphalocele, but were never found inside the sac. Umbilical cord cysts are commonly seen in patients with trisomy 18, 13 or other aneuploidy.…”
Section: Discussionmentioning
confidence: 91%
“…3,4,7 It is believed that growth retardation in these fetuses leads to an increased pressure at the umbilico-placental circulation and thereby leads to a sonographic appearance of a pseudocyst. 5 However, the present patient had a true cyst and no other anomalies were detected.…”
Section: [Received April 24 2006; Accepted December 13 2006]mentioning
confidence: 99%
“…There is no general consensus about the mode of delivery in the case of a large umbilical cord cyst, but Chen et al [6] reported that cesarean section was recommended to prevent intrauterine vascular compromise of umbilical blood flow during labor. Moreover, Sepulveda et al reported two cases of umbilical cord hematoma as serious complications of umbilical cord cystic masses, and umbilical cord hematoma might develop unexpectedly and rapidly, leading to intrauterine fetal death at any stage of pregnancy [1].…”
Section: Discussionmentioning
confidence: 98%
“…Pseudocysts also tend to be located close to the abdominal insertion of the cord, but it is not possible to discriminate between true cysts and pseudocysts with only ultrasonographic examination. Pseudocysts have no epithelial lining and originate from local degeneration or local edema of Wharton's jelly [1,6]. Prenatal detection of umbilical cord pseudocysts is important because they are strongly associated with fetal aneuploidy, other congenital anomalies such as omphalocele, and adverse perinatal outcomes [4,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…omphalocele, hydronephrosis, patent urachus etc) or chromosomal anomalies (trisomy 18, 13 or aneuploidy). [3][4][5]13 Intrauterine fetal demise has also been reported due to compression of umbilical vessels by these cystic swellings. 6 The present case is the first report of association of allantoic-urachus-vesical communication with proximal hypospadius and meatal obstruction.Because of a small defect in the allantoic cyst, urine was draining directly into the amniotic cavity thereby minimizing the morbidity of urethral obstruction.There was adequate liquor thus preventing Potter sequence and pulmonary hypoplasia.…”
Section: Discussionmentioning
confidence: 99%